Novel cardiac biomarkers (Serum S100A12 (Calgranulin C), FSTL1 (Follistatin-like 1), and Osteocalcin) in patients with Acute Chest Pain: Novel cardiac biomarkers in patients with Acute Chest Pain - Xie, Wenjing; Zhao, Wei; Wang, Hongtao; Xie, Yuanguang; Gu, Luyan (Journal of Medical Biochemistry, 2025)
Objective: To evaluate the impact of an optimized emergency care process on clinical outcomes and potential biochemical markers associated with acute chest pain (ACP). This study investigates whether improved emergency protocols can influence the release of key cardiac biomarkers and inflammatory mediators in ACP patients.Methods: A total of 116 ACP patients admitted to the emergency department were divided into a research group (RG) receiving optimized emergency nursing procedures and a control group (CG) receiving routine nursing procedures. Clinical parameters, including triage assessment time, emergency time, hospital stay, success rate of rescue, mortality rate, and incidence of adverse events, were compared. Additionally, serum levels of cardiac biomarkers (e.g., troponin I, creatine kinase-MB) and inflammatory markers (e.g., C-reactive protein, interleukin-6) were measured at baseline and at specified time points post-intervention to assess the biochemical impact of the emergency care intervention. Biomarkers such as S100A12 (Calgranulin C), FSTL1 (Follistatin-like 1), and Osteocalcin (hormonal biomarker)were also included to explore additional biochemical pathways relevant to cardiac stress, inflammation, and vascular function. Patient satisfaction was evaluated.Results: The RG showed significantly shorter triage assessment time, emergency time, and hospital stay compared to the CG (P
Keywords: S100A12 (Calgranulin C); FSTL1 (Follistatin-like 1); Osteocalcin; acute chest pain; optimized emergency nursing; cardiac biomarkers; inflammatory markers; biomarkers; rescue; adverse events; pain